'Blustering, bungling, trimming': Byron, Hobhouse, and the Politics of Don Juan Canto I. Issue 1 (1st June 2021) - Havard, John Owen
Abstract : This essay revisits the politics of Don Juan Canto I, taking cues from Byron's rejected portrait of Henry Brougham and his friendship with John Cam Hobhouse. Embarking on his career as an opposition politician, Hobhouse served as a foil to Byron; but for all his stern admonitions, his interventions and guidance were crucial to the future course of the poem. The cancelled 'Brougham stanzas' were overwhelmed by personal invective and scattershot critique. Guided by Hobhouse, Byron moved away from personal attacks of this nature, while expanding the poem's (encyclopedic) scope and honing its political purposes, including its satire of Tory authorities. While Hobhouse steered his way into power and became a member of the establishment he had once despised, Byron's poetry remains animated by contending political energies.